Pendidikan Pluralisme Beragama Menurut Purwa Ayu Mardi Utama - Arif Muzayin Shofwan; Miftakhul Rohman; Setyoadi Pambudi (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
Purwa Ayu Mardi Utama (PAMU) is one of the groups that affirm Javanese religious pluralism for the Javanese people. For PAMU, the Javanese religion is not a religion that wants to syncretize other religions that have recently entered the island of Java. Javanese religion is not a religion that wants to establish a new religion. However, the Javanese religion is an ordinance or rule from the ancestors of the island of Java that existed before the religions of other nations, such as Islam, Hinduism, Buddhism, Catholicism, Christianity, Confucianism, and the like entered the island of Java. This paper aims to examine the following matters, including (1) a brief biography of R.M. Djojopernomo, a founding figure of PAMU; (2) religious pluralism according to PAMU teachings; and (3) the experience of religious pluralism for PAMU at the local level.